Pemberian Akupresure dan Aromatherapy Fennel Oil Terhadap Peningkatan Produksi ASI - Putri, Rosalin Ariefah; Suryani, Heni; Puspitaningsih, Rezki (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Breastfeeding is a crucial process that requires adequate milk production to ensure the baby's health and growth. However, mothers may face difficulty in breastfeeding after giving birth due to insufficient milk production. To address this problem, intervention can be done through a combination of acupressure techniques and aromatherapy using essential fennel oil. This approach has been proven effective in increasing breast milk production and making the process smoother for the mother. The study aimed to determine the effect of acupressure and fennel oil aromatherapy in increasing breast milk volume. The research design was a quasi-experiment with a pretest and posttest group design. The study involved 30 breastfeeding mothers who met the inclusion criteria and were divided into two groups using purposive sampling. The results showed that there was a significant increase in breast milk production after providing acupressure techniques and fennel oil aromatherapy. The acupressure technique helped release oxytocin, which is essential in increasing breast milk production. Moreover, providing fennel oil aromatherapy during the acupressure process can help the mother become more relaxed and increase breast milk production. Therefore, we recommend that midwives use acupressure techniques and fennel oil aromatherapy as complementary therapies to help increase breast milk production and ensure a healthy breastfeeding experience for mothers and their babies.